PERAN HANAN ATTAKI DALAM MEMBANGUN PERSEPSI GENERASI MILENIAL TENTANG TUHAN (ANALISIS ISI ATAS VIDEO "KANGEN" DI YOUTUBE) - S. Dinar Annisa Abdullah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
This paper examines the content of the propaganda of Hanan Attaki on social media in an effort to spread goodness and religious messages, especially about divinity among young people. By using content analysis method, this paper attempts to describe in depth the contents of the information being reviewed, namely Hanan Attakiâ€™s youtube post with the theme â€œAllah Kangen Sera Hisâ€ published on December 6, 2017. This paper explains that in terms of content, the conception of God what was built by Hanan Attaki must be based on three interrelated aspects: 1) deep faith insight, 2) correct perception of God and 3) emotional aspects (faith) in the form of longing, missed, and ashamed of God. These three aspects of God must be in line with the true insight of God according to Islam. At the next stage, this perception must be manifested in the form of deep emotions towards God in the form of longing to do good and shame in doing evil. This paper also explains that Hanan Attakiâ€™s â€œKangenâ€ video content has received positive responses from netizens, especially among young people with high popularity (share, like, comment). The lively preaching carried out by Hanan Attaki on social media is able to build public perceptions, especially the millennial generation, about God in a simple way. This was supported by his distinctive rhetoric, style of language, voice and gestures and also a more relaxed and slender way of dressing to compensate for the dominant young children.